Factors Influencing use of Antibiotics for Patients with Pneumonia at Eduardo Ximenes Regional Hospital (EXRH), Baucau, Timor-Leste - Santos Ximenes, Herminia dos; Sarmento da Costa, Horacio; Soares de Araújo, Febriana; Carvalho Soares, Diana de; Almeida Oqui, Serafino de; Oqui, Maximiano (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Pneumonia is an acute respiratory infection that affects the lungs. The lungs are made up of small pockets called alveoli. In a healthy person, the alveoli are filled with air, but when a person is affected by pneumonia, the alveoli become filled with fluid or pus, causing difficulty in breathing and leading to symptoms such as feeling unwell. Objective: To explore the factors influencing the use of antibiotics in patients with pneumonia at Eduardo Ximenes Regional Hospital (EXRH) in Baucau, Timor-Leste. Research Methodology: The researchers employed a quantitative analysis approach with a cross-sectional design. Data collection was carried out using a purposive sampling technique to analyze the factors that influence the use of antibiotics for pneumonia patients at EXRH in Baucau, Timor-Leste. Results and Discussion: The results from EXRH indicated that many respondents had limited knowledge about pharmacodynamics, with 46 respondents (35.4%) reporting frequent lack of knowledge. Regarding pharmacokinetics, 50 respondents (38.5%) showed a lack of understanding, while 53 respondents (40.8%) demonstrated moderate knowledge of host factors. Conclusion: The survey results show that pharmacodynamic and host factors influence the use of antibiotics in patients with pneumonia, while pharmacokinetic factors did not appear to significantly impact antibiotic use.